Advanced engine performance diagnosis - Halderman, James D. 1943- (Prentice Hall, 2001)
Advanced Engine Performance Diagnosis, offers a practical, hands-on introduction to the diagnosis and troubleshooting of automotive engine control systems. It serves students as a single source for information on digital storage oscilloscopes, fuel injection and ignition system diagnoses, five-gas exhaust analysis, emission testing, and more-with a very technical, but easy-to-read and understand, presentation. This title meets the needs for a textbook that combines topics in engine performance (ASE A8 content area) and topics covered in the advanced engine performance (L1) ASE test content area. By combining these two complementary subjects into one comprehensive textbook, it is easier for the instructor to teach these topics and is cost effective for the student.